Avaliação de processos de dimensionamento de cortinas atirantadas - Pacheco, Cássio da Silva (2019)
The use of anchored retaining walls is a technical solution widely used in geotechnical works, whether in urban excavation or slope stabilization. One of the main issues on dimensioning is the way in which loads and anchors participate in the stability process. Two situations should be verified according to the first edition of the Brazilian Standard NB-565: the so-called external and internal failures. In the first case the anchors did not participate in the failure mechanism, and the Brazilian method, developed by Nunes and Velloso, was used in the analysis. The internal failure, analysed by the Ranke and Ostermayer method, considered the anchors in the failure mechanism. Nowadays are prevailing computer programs using Slice Methods. In those cases the anchor loads are considered in two ways: contributing to the moment equilibrium and increasing stresses at the base of the slices. In addition, it is possible to take into account the participation of the anchors in the failure mechanism. The present research analyses the design of anchored retaining walls, based on usual dimensions and typical soil properties of gneissic residual soil. A comparison between the simplified Bishop´s, Spencer and finite element methods, using commercial softwares, is undertaken.